Decreased Insulin Secretion but Unchanged Glucose Homeostasis in Cadmium-Exposed Male C57BL/6 Mice. (20th June 2019) - Li, Xiaoyin; Li, Mengyang; Xu, Jiming; zhang, Xiang; Xiao, Wei; Zhang, Zengli
Abstract : Cadmium (Cd) is a well-known toxic metal element that is largely distributed in the environment. Cd causes toxicity to most organs. Accumulating evidence suggests that Cd exposure is associated with islet dysfunction and development of diabetes, but the association remains controversial. The aim of this study is to evaluate the possible effects of chronic Cd exposure on glucose metabolism in male C57BL/6 mice. Mice were intraperitoneally injected with CdCl2 solution (1 mg.kg −1 ) twice a week for 24 weeks. Fasting blood glucose (FBG) levels and body weights were measured weekly. After 24 weeks, the intraperitoneal glucose tolerance test (IPGTT), intraperitoneal insulin tolerance test (IPITT), and fasting serum insulin (FSI) level test were performed. The insulin resistance index (HOMA-IR) and pancreatic β cell function index (HOMA- β ) were calculated and analyzed. The expression of insulin receptor (IR) in mouse liver was detected by real-time PCR. Pancreatic tissue was collected for histological examination. The results demonstrated that FBG, IPGTT, HOMA-IR, and HOMA- β were identical between Cd exposure and control mice. In contract, mean fasting serum insulin level, area under the curve (AUC) of IPITT, and IR expression in livers of Cd-exposed mice decreased significantly compared with control mice. Cd administration induced islet atrophy and decreased islet area. The results suggested that Cd exposure decreased insulin secretion and maintained glucose homeostasis in male C57BL/6 mice and that pancreatic functions should be monitored in populations chronically exposed to Cd.